E-Registration Application Read Al-Quran Development for Student's Institute of Informatics and Business Darmajaya - Triowali Rosandy; Retno Dwi Handayani; Pakarti Riswanto; Suratno Suratno (Proceeding International Conference on Information Technology and Business, 2022)
Registration the Quran Reading Development Program for Darmajaya Institute of Informatics and Business Students is currently still using the google form where the link is shared manually using social media such as WhatsApp, Instagram, Facebook or orally directly through lecturers teaching Islamic subjects. The Quran Reading Development Program Team opened registration for approximately 2 weeks to ensure that information on this activity had been conveyed to all students who had taken religious courses. Furthermore, the team took 1 week to validate the registration and payment data, then the Quran reading team publish information for students who succeeded or failed in registering. This causes the activity to experience problems where the implementation of the Bina Baca Quran program can run 3 to 4 weeks after the implementation of the learning lecture takes place. With the development of the use of electronic systems in community services, the Bina Baca Quran registration application is an Android-based mobile registration information system application that serves to facilitate students and teams in carrying out Quran reading development activities, especially during registration. The method in designing the Quran reading application for Darmajaya Institute of Informatics and Business students used is the SDLC method, namely the waterfall model. After testing and based on the results that have been done using blackbox testing, the Quran reading application can run smoothly as expected and there are no bugs and in the testing process. The registration application for the Quran reading development program is more efficient and can make it easier to carry out registration activities in the Quran reading development program for IIB Darmajaya students.Keywords— Registration, Quran Reading, Waterfall, Blackbox Testing, Android Mobile